The “Perfect” Antibiotic through the Eyes of Doctors, Pharmacists, and the General Public - R. I. Yagudina; K. A. Kopeyka; D. G. Karapetyan; M. V. Protsenko (Регуляторные исследования и экспертиза лекарственных средств, 2025)
INTRODUCTION. A rational approach to antibiotic selection is a key factor in the successful treatment of various infections, and it also reduces the risk of antimicrobial resistance. Under the current circumstances, it is particularly important to understand what criteria doctors and pharmacists consider when selecting antibiotics and what patients see as priorities. After all, it is often the patient-centred approach that determines both medication persistence and treatment effectiveness. Given that perceptions of the perfect antibiotic can vary greatly, it is important to summarise these perceptions and identify the key criteria that doctors, pharmacists, and the general public consider as priorities for antibiotic therapy (with treatment of lower respiratory tract infections as a case study).AIM. This study aimed to identify the opinions of doctors, pharmacists, and the general public on selecting the perfect antibiotic and on the current state of antibiotic therapy for lower respiratory tract infections.MATERIALS AND METHODS. This study included an opinion survey using questionnaires. The questionnaires were developed specifically for health professionals and antibiotic consumers. The sociological study involved 250 health professionals (doctors and pharmacists) and 150 respondents from the general public.RESULTS. The majority of health professionals (55.6% of doctors and 53.7% of pharmacists) believe that antibiotics are “very often” prescribed for lower respiratory tract infections. Health professionals think that the main factors contributing to antimicrobial resistance are “unjustified prescription of antibiotics” (21.0% of doctors and 24.1% of pharmacists), “overly frequent courses of antibiotics” (17.2% of doctors and 21.5% of pharmacists), and “errors in antibiotic selection” (16.9% for both groups). Most doctors (93.7%) and pharmacists (83.0%) actively instruct patients in the proper use of antibiotics. When selecting the perfect antibiotic, health professionals and the public prioritise efficacy, safety, and tolerability. The most significant factors in selecting antibiotics for children include minimal risk of allergic reactions, convenience of dosing, and availability of dose calculation guidelines. Syrup is the most preferable paediatric dosage form for all groups of respondents. Only 42.2% of doctors claim that they always provide patients with a prescription for antibiotics, and 53.3% of pharmacists regularly encounter customers without a prescription.CONCLUSIONS. This survey of doctors, pharmacists, and the public has identified cases of poor compliance with the regulations for dispensing and prescribing antibiotics on the part of doctors and cases of prescribing antibiotics without sound clinical justification, administering antibiotics without appropriate treatment-free intervals between courses, and making errors in antibiotic selection. Study materials may inform the development of recommendations on antibiotic treatment of lower respiratory tract infections to be used as part of continuing professional training curricula for specialists dealing with medicines throughout the pharmaceutical product lifecycle.